Comparative study of occurrence of recurrent aphthous stomatitis during exam stress and relaxed phase in dental college students of Krishna Institute of Medical Sciences - Mugdha Vijay Karambelkar; S R Ashwinirani; Abhijeet Sande; K A Kamala (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Recurrent aphthous stomatitis (RAS) is a common disease characterized by the development of painful recurring, solitary, or multiple ulcerations. RAS is classified according to different clinical variants as (1) minor (Miculiz's aphthae), (2) major (periadenitis mucosa necrotica), and (3) herpetiform ulcerations. AIM: The aim was to compare the occurrence of RAS during exam stress and relaxed phase in dental college students. METHODOLOGY: Selection criteria: (1) Inclusion criteria: All dental students who are willing to participate and exam-going students of year. (2) Exclusive criteria: Students who are not willing to participate in study during exam time. A total of 100 dental students were included in this study. History record and clinical examination was carried out in the Department of Oral Medicine and Radiology. The students were examined twice-during exam period (1 week prior to the exam) and in nonexam period. The data collection was done using a set of questionnaires. Statistical analysis was done using Microsoft Office Excel. RESULTS: In the present study, the occurrence of RAS was 50%. Majority of the students were in 20-21years age group. Out of fifty students, forty were females (80%) and ten (20%) were males. Stress was the most common factor which accounted for 68%. The most common site of occurrence was labial mucosa. In the present study, as students were under stress of exams once in 6 months, the appearance of RAS was found more (52%), followed by 3 months (38%) and very few students suffer once in a month (10%). In majority of students (82% of cases), RAS healed within a week. CONCLUSION: Based on the results of our study, the occurrence of RAS in dental college students was high 50%. On comparison of phases, the occurrence of RAS was high during exam period, which shows association with stress.